Better understanding of executive managers' features effect on small- and medium-sized service firms' risk-taking using multiple factors as control variables: fresh insights from emerging markets - Moh'd Anwer AL-Shboul (Cogent Business & Management, 2024)
The current study aims to measure the effect of executive managers (EMs) features on the risk-taking level in Jordanian small- and medium-sized service firms. For data analysis purposes, ordinary least squares regression analysis was utilized. We used the screening sample approach. A sample of 72 small- and medium-sized service firms was utilized to collect the data, such as health care, consumer goods, electrical and technology, media and entertainment, and tourism/hotels, noting that these firms were listed on the Amman Stock Exchange/Jordan in the period between 2018 and 2022 using a quantitative method and regression analysis technique. The study used specific features of EMs. We applied the formula 'RISKi,t = β0 + β1GDRi,t t + β2AGE i,t + β3QUAL i,t + β4EXPi,t + β5OWN i,t + β6DUAL i,t + β7TENRi,t + β8ROA i,t + β9BMV i,t + β10SIZE i,t + β11LEV i,t + β12LIQi,t + β13 R&D i,t + ε………(1)'. To measure the risk-taking degree in SME service firms, the return on assets (ROA) standard deviation (SD) coefficient was utilized using the Pearson correlation coefficient among all the study variables. The results conveyed that there is a substantial negative association between experience, ownership, risk-taking, and the qualifications of EMs. Moreover, the EM's tenure and the service firms' degree of risk-taking were proven to have a significant positive relationship. Finally, gender, age, the duality of EMs, and risk-taking degree were deemed unrelated.
Keywords: 650; EM's features; risk-taking; corporate governance; service firms; performance; Jordan